PENGARUH PENDEKATAN PEMBELAJARAN TEKNIS TERHADAP HASIL BELAJAR KETERAMPILAN SEPAKBOLA - Ricky Fernando (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is about to study the effectiveness of the technical learning approach to soccer skills learning outcomes. Theresults of this study is expected to serve as an alternative solution in order to improve the quality of learning soccer. Themethod used in this research is an experimental method with post-design design. The population in this research is thestudents of class XI SMA Labschool UPI Bandung as many as 60 students. The sampling technique used Purposive Samplingtechnique. Time of research is for 2 months, the number of treatment 18 times meeting, with frequency 1 week 3 times. Theauthor's chosen instrument is a soccer skill test. for high school students soccer skills test (early and final test of soccerskills) there are four that the author uses the test passing and stoping, heading, dribbling and shooting. Based on the resultsof the analysis it can be concluded: There is a significant influence of technical learning approaches to the results of learningsoccer skills.